An Integrative Proteomic/Lipidomic Analysis of the Gold Nanoparticle Biocorona in Healthy and Obese Conditions - Kobos, Lisa M. (Appl In Vitro Toxicol, 2019)
Introduction: When nanoparticles (NPs) enter a physiological environment, a coating of biomolecules or biocorona (BC) forms on the surface. Formation of the NP-BC is dependent on NP properties, the physiological environment, and time. The BC influences NP properties and biological interactions such as cellular internalization, immune responses, biodistribution, and others, leading to pharmacological and toxicological consequences. To date, examination of the NP-BC has focused primarily on protein components and healthy conditions. Therefore, we evaluated the protein and lipid content of BCs that formed on physicochemically distinct gold nanoparticles (AuNPs) under healthy and obese conditions. A comprehensive understanding of the NP-BC is necessary for the translation of in vitro toxicity assessments to clinical applications. Materials and Methods: AuNPs with two coatings (poly-N-vinylpyrrolidone [PVP] or citrate) and diameters (20 or 100 nm) were incubated in pooled human serum, and an integrated proteomic/lipidomic approach was used to evaluate BC composition. Macrophages were utilized to evaluate differential immune responses due to variations in the AuNP-BC. Results: AuNPs form distinct BCs based on physicochemical properties and the surrounding environment, with the obese BC containing more proteins and fewer lipids than the healthy BC. Differential macrophage inflammatory responses were observed based on AuNP properties and BC composition. Discussion and Conclusion: Overall, these findings demonstrate that AuNP size and coating, as well as physiological environment, influence the protein and lipid composition of the BC, which impacts cellular responses following exposure. These findings demonstrate that incorporation of BCs representing distinct physiological conditions may enhance the translatability of nanosafety in vitro studies.